Outsourcing success: critical managerial factors in the services sector - Nilakshi, W.K.G.; Musa, G. (International Journal Research Publications, 2012)
Competition in modern business is competition among business networks. In businesses, outsourcing has become a common practice. Managers‟ responsibility has broadened from managing business to managing business context including outsourcing. The overall aim of this paper is to develop a framework which considers all the important factors and their interactions in measuring outsourcing success. The framework is derived from the perspectives of resource dependency and social exchange theories. Degrees of outsourcing, vendor management capability and vendor‟s service performance, have been deduced as the most critical factors which influence outsourcing success. Compatibility between partners and partnership quality are proposed to respectively mediate and moderate the effect on outsourcing success.